2013
DOI: 10.4293/108680813x13693422521836
|View full text |Cite
|
Sign up to set email alerts
|

Deep Infiltrating Colorectal Endometriosis Treated With Robotic-Assisted Rectosigmoidectomy

Abstract: Robotic-assisted surgery for the treatment of deep infiltrating bowel endometriosis appears to be feasible, effective, and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 25 publications
(27 reference statements)
0
32
0
Order By: Relevance
“…Among them, 11 studies were non-comparative, i.e. included women operated with RAL only (Abo et al, 2016;Bedaiwy et al, 2013;Brudie et al, 2012;Collinet et al, 2014;Ercoli et al, 2012;Lim et al, 2011;Morelli et al, 2016;Neme et al, 2013;Nezhat et al, 2011;Pellegrino et al, 2015;Siesto et al, 2014), whereas six studies were comparative, i.e. compared two series of women operated with RAL and SL (Cassini et al, 2014;Dulemba et al, 2013;Magrina et al, 2015;Nezhat et al, 2010Nezhat et al, , 2015Nezhat and Sirota, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 11 studies were non-comparative, i.e. included women operated with RAL only (Abo et al, 2016;Bedaiwy et al, 2013;Brudie et al, 2012;Collinet et al, 2014;Ercoli et al, 2012;Lim et al, 2011;Morelli et al, 2016;Neme et al, 2013;Nezhat et al, 2011;Pellegrino et al, 2015;Siesto et al, 2014), whereas six studies were comparative, i.e. compared two series of women operated with RAL and SL (Cassini et al, 2014;Dulemba et al, 2013;Magrina et al, 2015;Nezhat et al, 2010Nezhat et al, , 2015Nezhat and Sirota, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…All involved cases were successfully completed using the robotic platform, with no conversion to laparotomy. In an overall review of current literature on robotic colon resection, Antoniou et al 7 3,4 Our case series represents one of first case series reporting the feasibly of successfully performing minimally invasive colonic resection and reanastomosis through the robotic platform in 3 patients with ovarian remnant syndrome and 1 case with secondary cytoreductive surgery for ovarian carcinoma without conversion to open laparotomy. The mean blood loss was 162.5 mL, and the mean length of hospital stay was 6.5 days until having flatus and a bowel movement.…”
Section: Discussionmentioning
confidence: 95%
“…2 Studies in the colorectal field have shown that the robotic approach is feasible and is associated with favorable surgical outcomes, as well as a lower rate of conversion to laparotomy, when compared with traditional laparoscopy. 3,4 Colorectal involvement is often seen in 3 gynecologic conditions: ovarian remnant syndrome, advanced endometriosis, and ovarian cancer. These disorders often require bowel resection for complete disease resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAL provides for precise dissection of the pelvic area, allowing good visualization of the pelvic plexus nerves, thereby allowing resection without nerve injury. The stable camera and freedom of movement allow for very delicate and accurate dissection, as well as identification and preservation of the superior hemorrhoidal artery, providing good irrigation to the rectal stump and diminishing the incidence of rectal fistula [28]. Current robotic systems do not provide tactile or haptic feedback to the operating surgeon, however.…”
Section: Discussionmentioning
confidence: 98%